Pengaruh Bauran Pemasaran 4P Terhadap Keputusan Pembelian Rumah Pada PT. Mahkota Tiga Puteri Kabupaten Tabalong - Fulqi Sulistiyono; Irwansyah (JURNAL BISNIS DAN PEMBANGUNAN, 2024)
Abstract: Competition in the business world is increasingly fierce, requiring business actors to have excellence in the products they produce. The large number of competitors operating in the same business sector increases the intensity of competition, so every company must have the right marketing strategy. in order to achieve the company targets that have been set and the most important thing is to achieve customer satisfaction. PT. Mahkota Tiga Puteri Tabalong Regency is one of the housing developers located in Tabalong Regency which provides houses of various types. Housing marketing generally uses the same attributes by paying attention to location, product, price and promise. PT. Mahkota Tiga Puteri, Tabalong Regency, has carried out a review of the market potential in the location that will be used as a housing complex, namely in the Sulingan area, Tanta District, Tabalong Regency. PT. Mahkota Tiga Puteri, Tabalong Regency, has carried out a review of the market potential in the location that will be used as a housing complex, namely in the Sulingan area, Tanta District, Tabalong Regency. In order to reach the Target Market, PT. Mahkota Tiga Puteri Tabalong Regency implements a marketing strategy, with 3 (three) strategies. Namely promotional strategies through advertising, distributing brochures to various potential consumers, and carrying out personal selling activities. The research results show that product quality has a significant effect on home purchasing decisions. Price does not have a significant effect on the decision to buy a house. Location has a significant influence on home purchasing decisions. Promotions have a significant effect on home purchasing decisions.   Keywords: Product Quality, Price, Location, Promotion, Purchasing Decisions